Structure of the macrozoobenthos community in Buai River, Pulau Tengah, Keliling Danau District, Kerinci Regency, Jambi Province - Juaninda, Nadya (Institute for Advanced Science, Social, and Sustainable Future, 2024)
Background: Buai River is a river located in the village of Jembatan Merah Pulau Tengah, Keliling Danau District, Kerinci Regency, Jambi. Sungai Buai with topographic conditions in the form of a hilly highland area, surrounded by mountains and dense forests so that it has a heterogeneous microhabitat and is still natural for macrozoobenthos. Therefore, a study was conducted on the presence and structure of macrozoobenthos in the Sungai Buai area of Central Island. This study aims to analyze the structure of the macrozoobenthos community based on the composition of the macrozoobenthos species, density, diversity, dominance and distribution of macrozoobenthos in the waters of the Buai River. This research is expected to provide information in the form of scientific data and knowledge about the structure of the macrozoobenthos community in the waters of the Buai River to be used as comparative data for future research. This research was conducted from January to February 2022. Method: The research method used is a quantitative descriptive method, which is to describe and evaluate a symptom or event that appears systematically. Determination of research stations is done by purposive sampling method, which is taken five stations based on environmental baseline. Data analysis was carried out by calculating the composition, macrozoobenthos density, Diversity Index, Dominance Index and Community Similarity Index between stations. Findings: The results showed that there were 5 classes, 11 orders, 26 families and 42 genera. Diversity values ranged from 1,4 to 2,45 which was classified as moderate, the dominance ranged from 0.1 to 0.45, and the similarity of the macrozoobenthic community in Sungai Buai 60.71% - 82.54% the similarity of the macrozoobenthos was relatively the same with little organic pollution. Conclusion: Based on the structure of the macrozoobenthos community in the Buai River, Central Island, it can be concluded that the Buai Pulau Tengah River, Keliling Danau District, Kerinci Regency, Jambi Province is still classified as very good. Novelty/Originality of this Study: This study presents novel findings by revealing the structure of the macrozoobenthos community in a relatively undisturbed highland river surrounded by dense forests, which provide a unique heterogeneous microhabitat. It contributes original data on the species composition, density, diversity, and distribution of macrozoobenthos in this specific region, offering a baseline for future comparative studies.